Study on the therapeutic potential of Dichroa febrifuga Lour. as a novel natural anticoccidial agent for Eimeria tenella infection in chicks - Guo, Zhiting; Li, Xinrong; Zhang, Shaobo; Wang, He; Luo, Xiaoqin; Liu, Yuan; Wei, Xiaocheng; Li, Chengyi (Frontiers in Veterinary Science, 2026)
Avian coccidiosis, caused by the parasite Eimeria tenella, significantly impacts the global poultry industry. The emergence of drug resistance and concerns about chemical residues in food make the development of effective natural alternatives imperative. This study aims to evaluate the therapeutic effects of Dichroa febrifuga Lour. (DFL) powder on broilers infected with E. tenella and explore its potential mechanisms. A total of 72 sixteen-day-old white-feathered broiler chicks were randomly allocated into four groups (each with six replicates of three chicks): Control, Model, DFL, and JQCS groups. Except for the Control group, all other groups were orally administered 5 × 104E. tenella oocysts. The DFL and JQCS groups were fed diets containing 0.1 g/kg DFL and 15 g/kg JQCS, respectively. We established an infection model in chicks and assessed the impact of DFL on growth performance, oocyst shedding, and cecal lesion scores. Histological examination and tight junction protein expression analysis were used to assess the integrity of the cecal tissue, and RT-qPCR and ELISA were employed to quantify local and systemic inflammatory responses. In addition, we used an LPS-stimulated HD11 macrophage in vitro model to verify the direct anti-inflammatory effects of DFL. In vivo, DFL treatment significantly improved growth performance, reduced oocyst shedding, and lowered cecal lesion scores, with an excellent anticoccidial index (>170). DFL also protected the intestinal barrier integrity by upregulating the expression of ZO-1, occludin, and claudin-1. More importantly, DFL significantly alleviated the inflammatory response by inhibiting the NF-κB and MAPK signaling pathways. In vitro, DFL exhibited a dose-dependent effect, significantly reducing the expression of inflammatory genes at low concentrations, while high concentrations showed pro-inflammatory effects. DFL demonstrated strong therapeutic effects against avian coccidiosis by inhibiting parasite proliferation, protecting the intestinal barrier, and modulating host inflammatory responses. These findings support the potential of DFL as an effective natural alternative for controlling poultry coccidiosis and highlight the importance of dose optimization in its application.